2021
DOI: 10.1055/a-1486-7497
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the Ottawa Score to Predict the Risk of Recurrent Venous Thromboembolism in Cancer Patients: The Prospective PREDICARE Cohort Study

Abstract: Introduction: Recurrent venous thromboembolism (VTE) despite curative anticoagulation is frequent in patients with cancer. Identifying patients with a high risk of recurrence could have therapeutic implications. A prospective study was designed to validate the Ottawa risk score of recurrent VTE in cancer patients. Methods: In a prospective multicenter observational cohort, adult cancer patients with a recent diagnosis of symptomatic or incidental lower limb deep vein thrombosis or pulmonary embolism were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…The Ottawa score is currently the only RAM available for predicting the risk of VTE recurrence in cancer patients. Developed by Louzada et al, in 2012 [15], this score has been assessed in several external validation studies with conflicting results [17,18,[23][24][25]. Applying the Ottawa score to cancer patients enrolled in the prospective TROPIQUE study who were treated with LMWHs for a confirmed index VTE failed to identify accurately those who developed recurrent VTE within 6 months, as reflected by an AUROC of 0.53 and an accuracy of 57.9%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ottawa score is currently the only RAM available for predicting the risk of VTE recurrence in cancer patients. Developed by Louzada et al, in 2012 [15], this score has been assessed in several external validation studies with conflicting results [17,18,[23][24][25]. Applying the Ottawa score to cancer patients enrolled in the prospective TROPIQUE study who were treated with LMWHs for a confirmed index VTE failed to identify accurately those who developed recurrent VTE within 6 months, as reflected by an AUROC of 0.53 and an accuracy of 57.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a high-risk Ottawa score (49.3%) had a 6-month pooled crude rate of recurrent VTE of 18.6% (95% CI 13.9-23.9) compared to 7.4% (95%CI 3.4-12.5) for those with a low-risk Ottawa score [16]. However, this score failed to identify patients at high risk of recurrent VTE in two recent large prospective studies [17,18], thereby questioning its reliability.…”
Section: Of 11mentioning
confidence: 98%
See 1 more Smart Citation
“…Consistently, our study found that being female was a risk factor for recurrence in patents with CAT. However, Girad et al 22 reported in their prospective cohort study that the Ottawa score failed to accurately predict recurrent VTE. Ahn et al 23 also failed to validate the Ottawa score in single-center, retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…56 When the risk score was applied and validated with the clinical trial data from the CLOT and CANTHANOX trials, it showed that a patient with a score of <0 had a low risk (5.1%), patients with a score of "0" had an intermediate risk (9.8%), and those with a score of !1 had a high risk (15.8%) of recurrent VTE. 56 However, in another prospective cohort study, the Ottawa score failed to predict the risk of VTE recurrence despite curative anticoagulation with LMWH in patients with CT. 57 More studies are required to validate the Ottawa score and to determine the best treatment option for cancer patients at risk of recurrent VTE.…”
Section: Recurrent Venous Thromboembolism During Anticoagulationmentioning
confidence: 99%